Effect of taping on multi-segmental foot kinematic patterns during walking in persons with chronic ankle instability. Issue 9 (September 2017) - Dingenen, Bart; Deschamps, Kevin; Delchambre, Frauke; Van Peer, Evelien; Staes, Filip F.; Matricali, Giovanni A.
Abstract: Objectives: To evaluate multi-segmental foot kinematic patterns in chronic ankle instability (CAI) participants during walking, and to investigate the influence of high-Dye and low-Dye taping on these kinematic patterns. Design: Cross-sectional study. Methods: Kinematic data of 12 non-injured controls and 15 CAI participants were measured with a three-dimensional motion analysis system during barefoot walking. In addition, the CAI participants walked with high-Dye and low-Dye taping. A rigid Plug-in gait model and the Rizzoli 3D Multi-Segment Foot Model were used to measure multi-segmental foot kinematic patterns. One-dimensional statistical parametric mapping was used to compare barefoot walking of the control and CAI group, and to evaluate differences between walking barefoot and walking with high-Dye and low-Dye taping within the CAI group. Results: Compared to the control group, CAI participants showed a decreased ankle dorsiflexion during loading response (p = 0.025) and a more inverted calcaneus in relation to the shank during the initial swing phase (p = 0.024). A more inverted position of the metatarsus in relation to the midfoot was observed after low-Dye taping during almost the entire stance phase (p = 0.017). No significant differences were found for high-Dye taping. Conclusions: Significant differences in kinematic patterns were found in the ankle joint and rearfoot, but not in the mid- and forefoot in CAI participants. The application of low-Dye taping resulted in a significantly increased inverted position of the forefoot, which can be considered as a less desirable effect for patients with CAI. No other effects of high-Dye and low-Dye taping on kinematic patterns were revealed.